DePEGylation strategies to increase cancer nanomedicine efficacy. Issue 2 (11th December 2018) - Kong, Li; Campbell, Frederick; Kros, Alexander
Abstract : PEGylation of nanoparticles prolongs circulation lifetimes and maximizes nanoparticle accumulation in target tumors. However, PEGylation comes at the cost of reduced cellular uptake of nanoparticles and concomitant drug delivery. This review discusses the various stimuli-responsive dePEGylation strategies that have been employed to overcome this "PEG dilemma". Abstract : To maximize drug targeting to solid tumors, cancer nanomedicines with prolonged circulation times are required. To this end, poly(ethylene glycol) (PEG) has been widely used as a steric shield of nanomedicine surfaces to minimize serum protein absorption (opsonisation) and subsequent recognition and clearance by cells of the mononuclear phagocyte system (MPS). However, PEG also inhibits interactions of nanomedicines with target cancer cells, limiting the effective drug dose that can be reached within the target tumor. To overcome this dilemma, nanomedicines with stimuli-responsive cleavable PEG functionality have been developed. These benefit from both long circulation lifetimes en route to the targeted tumor as well as efficient drug delivery to target cancer cells. In this review, various stimuli-responsive strategies to dePEGylate nanomedicines within the tumor microenvironment will be critically reviewed.